Analysis of physical vulnerability and threats to the Northern Longitudinal Highway in the micro‑regions of Metapán and Alto Lempa Norte, Northern Region, El Salvador - Barrera Morales, Alicia (2025)
The analysis of a 42 km section of the North Longitudinal Highway in El Salvador is developed in this work. It corresponds to the investigation thesis to obtain the degree of Master in Risk Management and Emergency Attention of the Postgrade Studies Program in Geology of the University of Costa Rica.  The work is based in the application of two methodologies that were developed and applied by the LanammeUCR in mountain highways in Costa Rica. One of then evaluates the susceptibility of land slipping, based on obtaining the critical angle through the average angle of the slope and its standard deviation in the slipped areas or prone to slips. The second methodology, evaluates the susceptibility of the highway to mud and detritus flows, based on the Kanji Methodology that considers the existence or combination of factors that influence the activation of this type of events.  These methodologies already used in Costa Rica, will be applied for the first time in El Salvador in the highway tract already described, giving valid results, which will contribute in its final design, that at this time is being developed by the local Government and the private company.